What in God's name are you eating? : how can Christians live and eat responsibly in today's global village? - Francis, Andrew, 1956- (Lutterworth Press, 2015)
"How you eat affects the planet-and everyone else on it. What you eat might literally cost the earth. It also has implications for your health, for the grower or producer, and for the way you think about the world. 'What in God's Name Are You Eating?' faces what many of us choose to ignore in the Western World: we, as adults, have allowed a childlike innocence to mask the real cost of the environment in which we are cocooned, while thousands elsewhere find themselves drought stricken and starving. "What in God's name are they are not eating?" "Enough" is the simple answer and we are part of the reason why."--Page 4 of cover